Zag : the number-one strategy of high-performance brands : a whiteboard overview - Neumeier, Marty (New Riders, 2006)
The author argues that in an extremely cluttered marketplace, traditional differentiation is no longer enough--today, companies need "radical differentiation" to create lasting value for their shareholders and customers. --from publisher description.